Jesus as teacher in the Gospel of Mark the function of a motif - Hershman, Evan ([London, England] T & T Clark Ltd, 2020)
"Evan Hershman seeks to examine Mark's portrayal of Jesus as teacher in comparison with portrayals of teachers in contemporary Greco-Roman literature, and argues that the teaching motif in Mark is used in highly distinctive ways. He argues that careful study reveals Mark's use of the trope does not aim to expound a fully fleshed-out ethical agenda, but rather to emphasize Jesus's unique authority, incorporate conflicts with other claimants to authority into the Gospel narrative, and persuade the gospel audience to accept his Christological vision and its demands on their lives. Hershman develops these three related themes behind the motif of moral instruction, and offers suggestions for how this portrayal of Jesus fits with the historical and social context in which the Gospel was written. By analyzing not only teaching and authority throughout Mark, but also numerous Greek and Greco-Roman texts concerning teachers and learning, Hershman creates a new reading of significant Markan passages - such as the parables discourse and the temple incident - in light of a focus on the importance of Jesus's teachings to the plot of the Gospel."--
Acknowledgements -- Introduction -- 1. Greek and Greco-Roman Texts on Teachers and Teaching -- 2. Teaching and Authority in the First Half of Mark -- 3. Teaching and Authority in the Second Half of Mark -- 4. Conclusion -- Bibliography -- Index of Ancient Sources -- Index of Modern Authors
Includes bibliographical references and index
Also published in print.
Reproduktion
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Jesus Christ -- Teachings; Jesus Christ -- Political and social views; Bible -- Criticism, interpretation, etc; Biblical studies & exegesis; Electronic books; Hochschulschrift